1979
DOI: 10.1128/jvi.32.2.536-545.1979
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Identity of Shared 5′-Terminal Sequences Between Genome RNA and Subgenomic mRNA's of B77 Avian Sarcoma Virus

Abstract: The polyribosomal fraction from chicken embryo fibroblasts infected with B77 avian sarcoma virus contained 38S, 28S, and 21S virus-specific RNAs in which sequences identical to the 5'-terminal 101 bases of the 38S genome RNA were present. The only polyadenylic acid-containing RNA species with 5' sequences which was detectable in purified virions had a sedimentation coefficient of 38S. This evidence is consistent with the hypothesis that a leader sequence derived from the 5' terminus of the RNA is spliced to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

1981
1981
1990
1990

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…The genomes of retroviruses assume multiple roles during the viral life cycle, serving as template for the synthesis of viral DNA by reverse transcriptase, messenger for the synthesis of several viral gene products, precursor for the genesis of subgenomic mRNA's, and vehicle for the transmission of viral genes from one host cell to another (1). Each of these roles involves structural features located in the vicinity of the 5' terminus of the viral genome: the initiation site for reverse transcription (41); a nucleotide sequence (R) repeated at the 5' and 3' termini of viral RNA that is required for chain propagation by reverse transcriptase (3a); a ribosome binding site and AUG codon required to initiate translation (29, 45); a splice donor site used in the genesis of subgenomic mRNA's (5,8,9,11,25,28,30,38,46); and a nucleotide sequence of uncertain size that is apparently necessary for incorporation of viral RNA into maturing virions (23,34). To facilitate the full elucidation of these functionally important features, we have determined the sequence of 1,010 nucleotides at the 5' end of the genome of the subgroup A Schmidt-Ruppin strain of Rous sarcoma virus (RSV).…”
mentioning
confidence: 99%
“…The genomes of retroviruses assume multiple roles during the viral life cycle, serving as template for the synthesis of viral DNA by reverse transcriptase, messenger for the synthesis of several viral gene products, precursor for the genesis of subgenomic mRNA's, and vehicle for the transmission of viral genes from one host cell to another (1). Each of these roles involves structural features located in the vicinity of the 5' terminus of the viral genome: the initiation site for reverse transcription (41); a nucleotide sequence (R) repeated at the 5' and 3' termini of viral RNA that is required for chain propagation by reverse transcriptase (3a); a ribosome binding site and AUG codon required to initiate translation (29, 45); a splice donor site used in the genesis of subgenomic mRNA's (5,8,9,11,25,28,30,38,46); and a nucleotide sequence of uncertain size that is apparently necessary for incorporation of viral RNA into maturing virions (23,34). To facilitate the full elucidation of these functionally important features, we have determined the sequence of 1,010 nucleotides at the 5' end of the genome of the subgroup A Schmidt-Ruppin strain of Rous sarcoma virus (RSV).…”
mentioning
confidence: 99%
“…The mRNA's of all three size classes are capped (7,23) and polyadenylated (15,46) and contain a common leader sequence at their 5' ends; this sequence apparently is spliced from a primary transcript of the RSV genome to the subgenomic mRNA's env and src (7,19,23,37,46). Previous studies of the mRNA's showed that the leader was composed of at least 104 nucleotides (7).…”
mentioning
confidence: 99%
“…Isolation of RNA. Total RNA was isolated from cells by phenol-chloroform extraction, as described previously (20). Cells were fractionated into nuclei and cytoplasm by lysis with 1% (vol/vol) Nonidet P40-1% (wt/vol) deoxycholate, and the polysomes were isolated by discontinuous sucrose gradients as previously described (8).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were fractionated into nuclei and cytoplasm by lysis with 1% (vol/vol) Nonidet P40-1% (wt/vol) deoxycholate, and the polysomes were isolated by discontinuous sucrose gradients as previously described (8). The fraction containing polyadenylic acid [poly(A)+] was isolated by oligodeoxythymidylic acid-cellulose chromatography (20). Determination of hybridization kinetics of viral cDNA to cellular RNA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation